Effect of music and movement group course on social skills in children with autism spectrum disorders - Peng, Jiaqi; Wan Abdullah, Wan Arnidawati; Chandrabose, Thanalactchumy; Mohamed Razali, Camellia Siti Maya (Taylor and Francis, 2025)
This study explores the impact of music and movement group courses on social skills in children aged 7 to 9 with Autism Spectrum Disorder (ASD). Conducted at a public school in China, 24 children were randomly assigned to experimental (n = 12) and control (n = 12) groups. Over 10 wk, the experimental group participated in a Dalcroze-based program featuring music and movement activities. Social skills were assessed using the Social Responsiveness Scale (SRS-2), focusing on Social Awareness, Cognition, Motivation, Communication, and Restricted Interests and Repetitive Behaviors. Results showed slight improvements in the experimental group, particularly in social communication and reduced restrictive behaviors, suggesting positive effects of music and movement on social skills in children with ASD.